PHARMACEUTICAL COMPOUNDS DETERMINATION IN WATER SAMPLES: COMPARISON BETWEEN SOLID PHASE EXTRACTION AND STIR BAR SORPTIVE EXTRACTION - Suazo, Fernanda; Vásquez, José; Retamal, Mauricio; Ascar, Loreto; Giordano, Ady (Journal of the Chilean Chemical Society, 2017)
A variety of organic compounds and their metabolites used in pharmaceutical and personal care products (PPCP´s) are continuously introduced into the environment by domestic or industrial wastewater. Solid phase extraction (polymeric dinivylbenzene cartridge) and stir bar sorptive extraction (polydimethylsiloxane phase) methodologies were optimized for the determination of some selected PPCP´s in aqueous matrices. Carbamazepine, β estradiol, 3-(4-methylbenzylidene) champhor, benzophenone-1 and ibuprofen were extracted from aqueous samples and methanol was used as conditioning/eluting solvent. The variables involved in the extraction of the analytes in the original sample were studied, pH between 3 and 6 and sample volume between 50 and 500 mL were considered. Three concentration levels were extracted at the optimal conditions of pH 5 and 500 mL of sample volume with a recovery up to 89%. The determination was performed in a GC-MS, and a derivatization step using BSTFA+TMCS (99:1) was needed previous to the injection. Real samples from Maipo River and Villarrica Lake were analyzed with the optimized method, and concentrations below the detection limit were detected.